1991
DOI: 10.1002/eji.1830210824
|View full text |Cite
|
Sign up to set email alerts
|

Developmental T cell receptor gene rearrangements: Relatedness of the α/β and γ/δ T cell precursor

Abstract: To examine the relationships between T cell populations at various stages of development, T cell receptor (TcR) gene rearrangements were compared between the four murine populations of (a) early thymocytes, (b) early splenocytes, (c) adult thymocytes and (d) adult splenocytes. TcR alpha gene rearrangements were shown to progress from 5' to 3' regions of the J alpha locus and from 3' to 5' regions of the V alpha locus during the development of T cells in both the thymus and spleen. Thus, the gene rearrangement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…thymocytes which have concomitantly rearranged a and 6 genes cannot mature further and die out before they are positively selected? This seems unlikely as the concomitant d 6 rearrangement pattern is extremely frequent throughout thymic development (fetal [see Table 11 and adult [21]). In fact, it has been demonstrated in at least two cases that a T cell with a concomitant d 6 rearrangement can mature to a functional T cell [9,23,241.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…thymocytes which have concomitantly rearranged a and 6 genes cannot mature further and die out before they are positively selected? This seems unlikely as the concomitant d 6 rearrangement pattern is extremely frequent throughout thymic development (fetal [see Table 11 and adult [21]). In fact, it has been demonstrated in at least two cases that a T cell with a concomitant d 6 rearrangement can mature to a functional T cell [9,23,241.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously demonstrated that mature T cell hybridomas derived from the spleen taken soon after birth share the high frequency of 5 ' J a gene rearrangements identified among fetal thymocytes. Conversely, adult thymocyte and splenocyte hybridoma populations preferentially utilize 3 ' Ja genes in rearrangement events [21].…”
Section: Discussionmentioning
confidence: 99%
“…Because most T cells from both ab and cd lineages rearrange TCRc (but not necessarily TCRa, TCRb, or TCRd) at an early stage of their development, the TCRc gene is the ideal target for the detection of T-cell clonality in human lymphomas. 2,3,11,12 In the dog, the TCRc locus is well characterized, consisting of 4 V region segments (V1-V4), 6 J region segments (J1-J6), and 4 C region segments (C1-C4). 15 Clonality assessment of T-cell populations that target the TCRc gene first used restriction fragment length polymorphism (RFLP) and Southern blotting, 13 which is an efficient but laborious and timeconsuming approach.…”
Section: Introductionmentioning
confidence: 99%
“…1A) (11). As a result of the genomic architecture of the ␣/␦ locus, TRAV-TRAJ rearrangements excise the TCR␦ gene segments; therefore, the developmental timing of TCR␣/␦ rearrangements must be tightly linked to the ␣/␤ versus ␥/␦ T cell fate decision (12). The repertoire of particular TRAV and TRDV gene segments remains restricted in the absence of selection, strongly suggesting that these restrictions occur at the level of V(D)J recombination (13).…”
mentioning
confidence: 99%